Intelligent digital hospitality ecosystem: A mobile-driven multi-criteria decision support system integrating Vikor-entropy optimization for strategic analytics - Hardini, Inkreswari Retno; Hermawan, Sabo; Nursafitri, Sintia; Usman, Osly; Nugroho, Mahendra Adhi (International Journal of Innovative Research and Scientific Studies, 2025)
This study addresses the lack of accessible and objective hotel information for tourists in Bandung by developing a mobile-based hotel recommendation system. The system integrates the VIKOR method for ranking alternatives and the Entropy method for weighting decision criteria objectively. Built using the Rapid Application Development (RAD) model, the application evaluates 48 hotels across Cibeunying, Bojonagara, and Karees regions based on four key criteria: price, location, facilities, and hotel class. Data were gathered through interviews with tourism officials, questionnaire responses from 100 tourists, and literature studies to ensure relevance and accuracy. The system allows users to adjust their preferences, generating personalized hotel recommendations based on their priorities. The results show that the application effectively produces consistent and meaningful rankings under different decision-making scenarios. The integration of VIKOR and Entropy enables more accurate, transparent, and adaptable recommendations that suit a wide range of tourist needs. This decision support system enhances the availability and quality of hotel information in Bandung, helping both domestic and international tourists make informed decisions. It also provides practical insights for hospitality stakeholders aiming to optimize their offerings and increase customer satisfaction